High pulse number transient heat loads on beryllium. (August 2017) - Spilker, B.; Linke, J.; Loewenhoff, Th.; Pintsuk, G.; Wirtz, M.
Highlights: ITER qualified S-65 beryllium was subjected to up to 10 7 transient heat pulses. A strong drop of the melting threshold from 10 2 to 10 3 pulses was observed due to fatigue effects. For a heat flux factor FHF ≤ 9 MW m −2 s 0.5 the damage saturated after 10 5 pulses. Beryllium demonstrated a promising performance for long-term operation if the transients remain below the determined saturation threshold. Further environmental conditions, e.g. particle fluxes and neutron irradiation, might alter the saturation threshold and the damage progression. Abstract: The experimental fusion reactor ITER will apply beryllium as first wall armor material. In present fusion experiments, e.g. ASDEX Upgrade, it has been detected that up to 25% of the plasma energy loss is deposited in non divertor regions during edge localized mode (ELM) events. Therefore, the impact of transient heating events on beryllium needs to be investigated to reliably predict the performance of the beryllium armor tiles under ITER operational conditions. In the present experiments, the electron beam facility JUDITH 2 was used to exert transient heat pulses with power densities of 0.14–1.0 GW m −2, as they can be expected for mitigated Type 1 ELMs in ITER, pulse durations in the range of 0.08–1.0 ms, and a number of pulses in the range of 10 3 –10 7 on S-65 beryllium specimens that were brazed on an actively cooled copper structure. Thereby, a strong drop of the melting threshold was discovered from a heat flux factor F HF = 22–25 MW m −2 s 0.5 for 10 2 pulses to F HF < 12 MW m −2 s 0.5 for 10 3 pulses. However, a saturation of the thermally induced damage was observed for F HF ≤ 9 MW m −2 s 0.5 after 10 5 pulses. This result indicated a promising performance of beryllium under a high number of transient heat pulses in ITER. Nevertheless, the synergistic effects between thermal loads, particle loads, and neutron irradiation might affect the saturation threshold and need to be investigated in future studies.